Practices and spaces by gender: landscapes and rural tasks of livestock producers of the Sierras Chicas from Córdoba, Argentina - Arias Toledo, Bárbara; Trillo, Cecilia (Ethnobiology and Conservation, 2018)
The present contributions shows as the gender role and the economic way of life of people have influence among landscape perception and classification. Data were obtained by the use of semistructured surveys aimed at criollo cattle ranchers in the mountains of Córdoba and index of cultural significance, economic value and statistical differences by gender were calculated. It is observed the domestic role of women as a cultural guide of these population, which determines their action in the different perceived units of landscape. Also was verified that the domestic units have greater degrees of classification, and that such classification is related to their practice of generalist breeding. Likewise, vegetation management practices related to their occupation are also revealed.